A novel approach to prepare efficient CO2 sorbents derived from alumina-extracted residue of coal ash. Issue 6 (December 2021) - Li, Xiangyu; Wang, Zhiqing; Feng, Ru; Huang, Jiejie; Fang, Yitian
Abstract: If a large amount of fly ashes produced by coal-fired power plants was not treated harmlessly, it will pose a serious threat to the ecological environment. As one of the high-valued utilization technologies of fly ash, the technology of extracting aluminum from coal ash produces large quantities of waste residue after acid leaching nevertheless. It is an economic and environmentally friendly way to recycle alumina-extracted residue (AR) as solid sorbent to capture CO2 . In this study, using AR as raw material, we synthesized PEI modified solid sorbents by novel "wet gel impregnation" method (WGI) to enhanced CO2 capture. The effects of amine loading, adsorption temperature, and impregnation method on CO2 adsorption capacity and kinetics were investigated by thermogravimetric analysis (TGA). On this basis, a possible double-layer adsorption model was proposed, i.e., the PEI adsorption layer on the outer surface of sorbents and the internal isolation layer. The ratio of the two layers changed with the variation in PEI loading and adsorption temperature, resulting in the difference of adsorption capacity. The maximum CO2 adsorption capacity of 2.07 mmol/g was obtained under the amine loading of 40 wt% at 95 °C, and 100% CO2 . Moreover, the stable adsorption capacity and high CO2 selectivity were maintained in five repeated adsorption-desorption cycles. Graphical Abstract: ga1 Highlights: Alumina-extracted residue of coal ash (AR) was modified with PEI to fabricate CO2 sorbents. A novel preparation method superior to conventional wet impregnation has been successfully developed. AR-40PEI-WGI exhibited the highest CO2 adsorption capacity and good cycle stability. Proposed CO2 adsorption model and mechanism of amine sorbents was discussed. Recycling solid waste AR owned both environmental protection and cost advantages.